Analisis Kebutuhan Pengembangan Multimedia Interaktif CIFITAGA pada Pembelajaran Pendidikan Pancasila Siswa Kelas II Sekolah Dasar - Marcella Rara Priani; Kharisma Eka Putri; Sulistiono Sulistiono (YASIN, 2026)
Pancasila Education learning in elementary schools is still dominated by conventional methods that lack variety, so it has not been able to optimize students’ engagement and understanding. This condition indicates the need for innovative interactive learning media that are appropriate to the characteristics of elementary school students. This study aims to analyze the need for developing CIFITAGA interactive multimedia on the topic of physical characteristics among family members. This study used a qualitative approach with a descriptive design, involving 28 students and one Grade II teacher selected through purposive sampling. Data were collected through observation, interviews, and questionnaires, and were then analyzed using qualitative descriptive analysis techniques. The results show that Pancasila Education learning is still teacher-centered with limited use of media, so students tend to be passive and experience difficulty understanding the material. Students also more easily understand the material through visual and audio media and show interest in interactive learning. This finding confirms that CIFITAGA interactive multimedia is needed to support a more engaging, active, and student-centered Pancasila Education learning process. This study provides practical implications for elementary school teachers in designing interactive learning media that are appropriate to students’ learning needs and characteristics.